Reactive Molecular Dynamics Simulations of Sodium Silicate Glasses — Toward an Improved Understanding of the Structure. (10th November 2016) - Yu, Yingtian; Wang, Bu; Wang, Mengyi; Sant, Gaurav; Bauchy, Mathieu
Abstract : Reactive potentials are becoming increasingly popular as they are expected to bridge the gap between ab initio and classical molecular dynamics. However, their applicability and potential benefits to model multicomponent glass networks are yet to be assessed. Here, an archetypal modified silicate glass, sodium silicate glass, is simulated using the ReaxFF potential. The predicted structure is critically evaluated and compared to that obtained by a classical potential and experimental data. Our results indicate that ReaxFF offers an improved description of the atomic structure, both at the short‐ and medium‐ range. Particularly, owing to its bond order form that dynamically adjusts potential energies according to the local atomic environment, ReaxFF reproduces the effect of modifiers on the Si–O network, a demonstration of its good transferability to various compositions. Overall, ReaxFF provides a promising alternative to classical and ab initio methods for simulating complex structures and processes for multi‐component silicate glasses.